Comparative Study of Registered Nurse and Specialist’s Attitude Toward Nurse-Physician Collaboration in Hospital - Setiawan Setiawan (Jurnal Ners, 2013)
Introduction: Relationships between nurse and physician in hospital in Indonesia have been established for a long time. This relationship keeps continue toward more professional in order to enhance quality of healthcare. The purpose of this study was to identify attitude of registered nurse and specialist toward nurse-physician collaboration in hospital.Methods: Descriptive comparative design was employed in this study. Number of respondents recruited was 87 which composed of 44 registered nurses and 43 specialists). Data was collected by using Jefferson scale of attitudes toward nurse-physician collaboration. Gathered data was analyzed by simple statistics (frequency and mean) to describe demographical data and by independent t-test to determine the attitude difference between registered nurses and specialist toward nursephysician collaboration.Results: Results of this study showed that registered nurses and specialist have positive attitude toward nurse-physician collaboration at H. Adam Malik General Hospital. Based on independent t-test, this study found that registered nurses signi fi cantly has more positive attitude toward nurse-physician collaboration in hospital compare to specialist.Discussion: It is recommended that registered nurses and specialist at H. Adam Malik General Hospital should develop a collaboration model in hospital to ensure quality hospital-based health service.